E-Planning and Collaboration 2018
DOI: 10.4018/978-1-5225-5646-6.ch069
|View full text |Cite
|
Sign up to set email alerts
|

Concerns Management, E-Government and E-Participation

Abstract: Advancements in internet technology have profoundly changed communication between citizens and government authorities. Concerns management systems and smartphone applications offer new and convenient channels of interaction. In Germany, the “Mängelmelder” platform offers a nationwide service channel for local citizens' concerns. Citizens generally use this communication channel for reporting public infrastructure defects. This paper examines whether the “Mängelmelder” platform – with customized systems can fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Sin embargo, la información que se extrae y la manera en que se organiza e interpreta hace uso de categorías de tecnología como: Estas tecnologías, en sí mismas, no son e-Participación, pero se presentan como instrumentos para la ejecución de los objetivos de la Participación Ciudadana. A través de medios intercedidos por las TIC se crean nuevas maneras y se establecen mejores métodos que impulsen la cultura institucional y la toma de decisiones (Santamaría-Philco et al, 2016;Vaerst et al, 2018;Zheng & Schachter, 2018).…”
Section: E-participaciónunclassified
“…Sin embargo, la información que se extrae y la manera en que se organiza e interpreta hace uso de categorías de tecnología como: Estas tecnologías, en sí mismas, no son e-Participación, pero se presentan como instrumentos para la ejecución de los objetivos de la Participación Ciudadana. A través de medios intercedidos por las TIC se crean nuevas maneras y se establecen mejores métodos que impulsen la cultura institucional y la toma de decisiones (Santamaría-Philco et al, 2016;Vaerst et al, 2018;Zheng & Schachter, 2018).…”
Section: E-participaciónunclassified
“…The first empirical research identified was the work of Chu, Yeh and Chuang (2008), a case stuty in Taiwan. We also identified case studies in Germany (Vaerst et al, 2015), Iran (Akhondzadeh-Noughabi et al, 2013), Portugal (Duque et al, 2013) and Tehran (Keramati et al, 2011). Literature encompasses cluster analysis to understand citizen satisfaction (Ghodousi et al, 2016) and citizens' complaints (Ghodousi et al, 2019).…”
Section: Box 1 Articles About Cirmmentioning
confidence: 99%
“…The problem is that almost every author uses his or her name for it. Some of them use broad term Citizen Relationship Management (e.g., Vaerst, 2015;Hartmann et al, 2017), another used 311 number as the name for all channels to report the issue (e.g., Clark and Shurik, 2016 Citizen reporting means that citizens actively report some incidents or issue they witnessed. Different urgency of such reports distinguishes emergency and non-emergency incidents.…”
Section: Citizen Reporting On Issues Of Public Infrastructure (Crispi)mentioning
confidence: 99%